Factors Affecting Adoption of Home Science Practices Disseminated Through Rural Awareness Work Experience (RAWE) - Kaur, Sandeep; Mann, Sukhdeep Kaur; Kaur, Manjot (Indian Journal of Extension Education, 2021)
The study was aimed to assess the adoption status of home practices and to identify theÂ various factors affecting adoption and non-adoption of practices disseminated through rural awareness work experience programme. The study was conducted in four villages ofÂ Ludhiana district of Punjab state, where RAWE programme was conducted during the year 2013-14 to 2016-17. A total of 120 respondents constituted the sample of the study. Data were collected through a well- structured and pre tested interview schedule. Highest adoptionÂ status was achieved by the practices under â€˜Food and Nutritionâ€™ followed by practices under â€˜Human Developmentâ€™ discipline. Various factors affecting adoption of different practices as reported by the respondents were personal interest, saves resources andÂ provides satisfaction. Major factors affecting non-adoption of practices were lack of interest, lack of resources, non-availability of raw material and inadequate skill retention. MajorityÂ of the respondents suggested that practices imparted under RAWE programme should be cost effective, for better adoption. Respondents also suggested that to increase adoption rate of home science practices, duration of RAWE should be increased, so that respondentsÂ can get sufficient time to learn new practices.